Kombinasi Metode Certainty Factor dan Forward Chaining Dalam Sistem Pakar Diagnosis Mandiri Mental Illness - Diana, Dwi Rahmadani Ivan; Samsudin, Samsudin; Irawan, Muhammad Dedi (STMIK Banjarbaru, 2023)
Mental illness or psychiatric disorders are syndromes that disrupt a person's thinking pattern or psychology, causing dysfunction in daily activities. Data collected in Indonesia's health profile shows a high prevalence of untreated mental disorders. This is in stark contrast to the number of psychologists and psychiatrists available in the country. Society's stigma against mental disorders causes many to consider it mystical and reluctant to get themselves checked. This research uses certainty factor and forward chaining methods to overcome uncertainty in analyzing information from experts. The application is built based on Android which will make it easier for patients to access and diagnose the disease they are suffering from. By calculating mental illness diagnoses involving 62 symptoms and 10 diseases, the combination of certainty factor and forward chaining methods produces the same system and expert accuracy values. This shows the effectiveness of both approaches when combined.Keywords: Expert System; Forward Chaining; Certainty Factor; Mental IllnessÂ AbstrakPenyakit mental atau gangguan kejiwaan adalah sindrom yang mengganggu pola pikir atau psikologi seseorang, menyebabkan disfungsi aktivitas sehari-hari. Data yang dikumpulkan dalam profil kesehatan Indonesia menunjukkan tingginya prevalensi gangguan jiwa yang tidak diobati. Ini sangat kontras dengan jumlah psikolog dan psikiater yang tersedia di negara ini. Stigma masyarakat terhadap gangguan jiwa menyebabkan banyak yang menganggapnya sebagai hal mistis dan enggan memeriksakan diri. Penelitian ini menggunakan metode certainty factor dan forward chaining untuk mengatasi ketidakpastian dalam menganalisis informasi dari pakar. Aplikasi yang dibangun berbasis android yang akan memudahkan pasien dalam mengakses dan mendiagnosa penyakit yang diderita. Dengan penghitungan diagnosa mental illness yang melibatkan 62 gejala dan 10 penyakit, kombinasi metode certainty factor dan forward chaining menghasilkan nilai akurasi sistem dan pakar yang sama. Hal ini menunjukkan keefektifan kedua pendekatan tersebut jika digabungkan.Â